Deciphering the Mechanism of Xijiao Dihuang Decoction in Treating Psoriasis by Network Pharmacology and Experimental Validation - Guo Y; Gan H; Xu S; Zeng G; Xiao L; Ding Z; Zhu J; Xiong X; Fu Z (Dove Medical Press, 2023)
Yicheng Guo,1 Huiqun Gan,1 Shigui Xu,1 Guosheng Zeng,2 Lili Xiao,2 Zhijun Ding,2 Jie Zhu,3 Xinglong Xiong,3 Zhiyuan Fu1 1Department of Pharmacy, Dermatology Hospital of Jiangxi Province, Nanchang, People's Republic of China; 2Jiangxi Provincial Clinical Research Center for Skin Diseases, Nanchang, People's Republic of China; 3Candidate Branch of National Clinical Research Center for Skin Diseases, Nanchang, People's Republic of ChinaCorrespondence: Zhiyuan Fu, Department of Pharmacy, Dermatology Hospital of Jiangxi Province, 388, Yinbing Road, Nanchang, Jiangxi, People's Republic of China, Tel +86 13970827820, Email fuzhiyuan0774@yeah.netPurpose: This study aims to confirm the efficacy of Xijiao Dihuang decoction (XJDHT), a classic prescription, in treating psoriasis and to explore the potential therapeutic mechanism.Methods: For pharmacodynamic analysis, a mouse model of imiquimod cream (IMQ)-induced psoriasis was constructed. Active ingredients and genes of XJDHT, as well as psoriasis-related targets, were obtained from public databases. Intersecting genes (IGEs) of XJDHT and psoriasis were collected by Venn Diagram. A protein-protein interaction (PPI) network of IGEs is constructed through the STRING database. The Molecular Complex Detection (MCODE) and Cytohubba plug-ins of Cytoscape software were used to identified hub genes. In addition, we conducted enrichment analysis of IGEs using the R package clusterProfiler. Hub genes were validated via external GEO databases. The influence of XJDHT on Hub gene expression was examined by qPCR and ELISA, and molecular docking was used to evaluate the binding efficacy between active ingredients and hub genes.Results: The results revealed that XJDHT possesses 92 potential genes for psoriasis, and 8 Hub genes were screened. Enrichment analysis suggested that XJDHT ameliorate psoriasis through multiple pathways, including AGE-RAGE, HIF-1, IL-17 and TNF signaling pathway. Validation data confirmed the differential expression of IL6, VEGFA, TNF, MMP9, STAT3, and TLR4. Molecular docking revealed a strong affinity between active ingredients and Hub genes. The efficacy of XJDHT in improving psoriatic lesions in model mice was demonstrated by PASI score and HE staining, potentially attributed to the down-regulation of VEGFA, MMP9, STAT3, TNF, and IL-17A, as evidenced by ELISA and qPCR.Conclusion: This study employed network pharmacology and in vitro experiments to identify the potential mechanisms underlying the therapeutic effects of XJDHT on psoriasis, providing a new theoretical basis for its clinical application in the treatment of psoriasis.Keywords: psoriasis, Xijiao Dihuang decoction, network pharmacology, molecular docking, angiogenesis